Learning Character of Early Childhood Students in Elementary Schools Through Utilization of Facilities and Infrastructure - Ahmad Calam; Suardi Yakub; Ilham Nazaruddin; Ronald Mahmud; Abdul Halim (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study is to describe the minimum standard of classroom facilities, the use of infrastructure in the process of character building in learning, the advantages and factors that hinder teachers from using infrastructure in the learning process at SD PAB Deli Serdang. The object of this research is the early grade elementary school students who are in the early age phase. This study uses a quantitative qualitative research (Mixed Methods) design. Technique data collection using observation, interviews, documentation and field notes. The data analysis technique used is analysis before in the field, analysis while in the field (data reduction, data presentation, verification), analysis after completion in the field. The results of the study indicate that meeting the standards of classroom facilities, utilization of facilities in the learning process, the advantages of teachers are being able to make maximum use of classrooms, following procedures for using educational infrastructure carefully and carefully